Relationship between item difficulty and discrimination indices in true/false-type multiple choice questions of a para-clinical multidisciplinary paper. - Sim, Si Mui; Rasiah, Raja Isaiah (Academy of Medicine, Singapore, 2006)
INTRODUCTION: This paper reports the relationship between the difficulty level and the discrimination power of true/false-type multiple-choice questions (MCQs) in a multidisciplinary paper for the para-clinical year of an undergraduate medical programme.